Fundamental research statistics : for the behavioral sciences - Roscoe, John T. (New York : Holt, Rinehart and Winston, 1969)
This text is intended to provide an introductory treatment of research statistics for the student in education and psychology.
Includes index.
rpm 25/01/2019
Loans
Keywords: Statistics